Estimation of variants of the pancreatic gland pathology in patients, suffering complicated forms of chronic pancreatitis in late postoperative period - V. M. Ratchyk; D. V. Orlovsky; A. V. Tuzko; O. P. Petishko (Клінічна хірургія)
Objective. Estimation of variants of the pancreatic gland pathology and rate of the unfavorable results occurrence in late postoperative period in patients, suffering  complicated forms of chronic pancreatitis, depending on the procedures of surgical treatment.